Quantification of evaporation water losses from nearly 5000 reservoirs in China - Yinuo Zhu; Aizhong Ye; Wei Tian (Journal of Hydrology: Regional Studies)
Study region: China, focusing on 4863 inland reservoirs with areas greater than 1 km2. These reservoirs are crucial for water supply and management, and understanding the invisible water losses they incur is vital for assessing surface water availability. Study focus: This study reconstructs the monthly area series of 4863 inland reservoirs in China from 1988 to 2018 utilizing the latest reservoir database and water enhancement algorithm. Reservoir evaporation is quantified based on the reconstructed area series and a lake evaporation algorithm based on Penman equation and accounting for heat storage and fetch effect. Long-term and seasonal trends are analyzed, and driving factors behind these trends are identified using a detrending method. New hydrological insights for the region: The total area of China's reservoirs increased at a rate of 132.68 km²/year, with a cumulative growth of 2880.7 km² in existing reservoir. A significant negative correlation was observed between seasonal variations in reservoir area and precipitation. The long-term average evaporation volume from reservoirs was 18.55 × 10⁹ m³ /year, with an increasing trend of 1.46 × 10⁸ m³ /year and an evaporation rate increase trend of 0.0045 mm/day per year, primarily driven by temperature. Seasonal evaporation rates lagged one month behind temperature trends, peaking in September. These findings provide essential data support for reservoir management and water resource planning, offering insights into addressing water supply and sustainability challenges under future climate changes.